Can communication by the government improve trust and reduce risk perception?. (3rd July 2019) - Lee, Dae Woong
ABSTRACT: The question addressed in this research is: Does a higher level of government risk communication regarding the location policy of risk facilities increase the public's trust in the government and reduce risk perception? Based on a theoretical discussion, this study subdivided risk communication into participation, deliberation, and information transparency. The effects of each on government trust and risk perception were analyzed using a structural equation model (SEM). The results showed that guaranteeing various stakeholders' participation and their roles in regard to the policy for locating high-risk facilities improved trust in the government, and thereby decreased risk perception. Second, the process of deliberation improved trust in the government as the administrator of risk management and effectively decreased negative risk perception. Third, providing transparency and sufficient information to the public did not have a statistically significant effect on government trust, but reduced risk perception.